Microporosity and parent body of the rubble-pile NEA (162173) Ryugu - Neumann, Wladimir; Grott, Matthias; Trieloff, Mario; Jaumann, Ralf; Biele, Jens; Hamm, Maximilian; Kührt, Ekkehard (Icarus, 2021)
Both observations of C-type near-Earth asteroids and laboratory investigations of carbonaceous chondritic meteorites provide strong evidence for a high microporosity of C-type asteroids. Boulder microporosity values derived from in-situ measurements at the surface of the rubble-pile NEA (162173) Ryugu are as high as 55 %, which is substantially higher than for water-rich carbonaceous chondrite samples and could indicate distinct evolution paths for the parent body of Ryugu and parent bodies of carbonaceous chondrites, despite spectral similarities. In the present study, we calculate the evolution of the temperature and porosity for early solar system's planetesimals in order to constrain the range of parameters that result in microporosities compatible with Ryugu's high-porosity material and likely burial depths for the boulders observed at the surface. By varying key properties of the parent body, such as accretion time t0 and radius R that have strong influence on temperature and porosity and by comparing the interior porosity distribution with the measured boulder microporosity, hydration, and partial dehydration of the material, we constrain a field within the (R,t0)-diagram appropriate for bodies that are likely to have produced such material. Our calculations indicate a parent body size of only a few km and its early accretion within ≲2 − 3 Myr after the formation of Ca-Al-rich inclusions (CAIs). A gradual final porosity profile of best-fit bodies indicates production of both low- and high-density boulders from the parent body material. By contrast, parent body properties for CI and CM chondrites obtained by fitting carbonate formation data indicate a radius of ≈20 − 25 km and an accretion time of ≈3.75 Myr after CAIs. These results imply a population of km-sized early accreting highly porous planetesimals as parent bodies of the rubble-pile NEA Ryugu (and, potentially, other NEAs) and a population of larger and late accreting less porous planetesimals as parent bodies of water-rich carbonaceous chondrites.
Available online 24 October 2020
Gesehen am 07.04.2021